PEMBAHARUAN USHUL FIQH ALI JUM’AH MUHAMMAD - Muhammad Zainuddin Sunarto; Tutik Hamidah; Abbas Arfan (JURNAL HAKAM, 2022)
The reform of ushul fiqh is perhaps the most significant achievement in the rebirth of Islamic philosophy. Only when people realize the phenomenon of stagnation of traditional fiqh can ushul fiqh be renewed. This awareness can only be built if people realize the need for reform of religious thought and practice it on a large scale. Many scholars propose a reconstruction of ushul fiqh, intending to show that religion can be used to solve everyday problems. Sheikh Ali Jum'ah, Izzudin Ibn Abdus Salam, and Ibn Ashur were prominent figures. Brilliant ideas and practical solutions seem to have entered the paradigm of Indonesian Islamic thought, especially the paradigm of ushul fiqh reform, which is still stagnant. Another weakness of fiqh and ushul fiqh is that there is no dynamic relationship between them and the social sciences, thus losing their relevance to the needs of the people. The mufti of Egypt, Sheikh Ali Jum'ah, also had the same view regarding the reformulation of Usul fiqh produced by previous scholars. So that Usul fiqh can be more developed and adaptive to new problems. Sheikh Ali Jum'ah's tajdid offer, namely: Restoring the old study form of ushul fiqh with an updated structure; Returning several views on several issues and using new opinions on existing problems, as well as reusing aqli in discussing these problems; Returning some views on the application of the rules to this science and in this application sticking to other views; Restoring this scientific structure by the novelty of the illat, and make this renewal according to the character of ushul fiqh according to their respective streams.